The Use of Digital Learning Media to Strengthen Digital Literacy of Drama Texts at Al Islam Boarding School Junior High School - Jeni Hamzah; Alfian Rokhmansyah; Irma Surayya Hanum; Elvira Azzahra Ramsi; Teguh Prakoso (Raja Zulkarnain Education Foundation, 2026)
This study aims to analyse the effect of digital learning media use on strengthening the digital literacy of eighth-grade students at SMP Al Islam Boarding School, Cirebon, in Indonesian language learning through drama texts. The research was conducted during the second semester of the 2024/2025 academic year. The participants were 25 students from Class VIII D, selected through purposive sampling. A quantitative approach with a one-group pretest-posttest quasi-experimental design was employed, supported by qualitative data from classroom observation and teacher interviews within a sequential explanatory framework. The primary instrument was a digital literacy questionnaire administered in two stages, pre-test and post-test, measuring four dimensions of digital literacy: digital skill, digital ethics, digital safety, and digital culture. The treatment involved integrating YouTube as a video display medium for drama performances and Google Search Engine as a reference source for collaborative scriptwriting tasks. Quantitative data were analysed using descriptive statistics in Microsoft Excel, while qualitative data were analysed using data reduction, data display, and conclusion drawing. The results revealed an increase in the mean digital literacy score from 61.4 to 68.16, with the proportion of students in the High category rising sharply from 24% to 76%, and no students remaining in the Low category following the intervention. Qualitative findings further confirmed increased student enthusiasm and active engagement throughout the learning sessions. It is concluded that integrating digital learning media significantly and positively strengthens students' digital literacy within the boarding school context.